Managing electronic records in corporate records & information management systems : a records & information management 2-day training course for government and private enterprise (Lorson Resources Limited ChaguanasTT, 2012)
Presents the manual prepared for participants attending the training course.
Keywords: RECORDS MANAGEMENT